Hybrid Deliberation and Under-Represented Groups: From Presence to Influence in Deliberative Design - Marsili, M. (International Research Workshop on Deliberative Practices and Under-Represented Groups, 2026)
This paper asks whether deliberative processes that include under-represented groups also give them influence, or only presence. It argues that inclusion should be assessed through three linked concerns raised by the workshop call: how under-represented groups are defined, how deliberative arenas relate to formal institutions, and how procedures are designed to prevent exclusion. In hybrid settings, digital mediation can shape who is invited, seen, heard, and ultimately taken seriously. The paper develops a four-part framework—access, visibility, voice, and uptake—to show why formal openness does not necessarily produce democratic inclusion. It also connects deliberative democracy, epistemic injustice, and algorithmic mediation with work on synthetic reality, cognitive warfare, and digital governance. The practical implication is that hybrid deliberation should be designed as an institutional ecology, not just a discussion format.